Pseudodoping of a metallic two-dimensional material by the supporting substrate - Bin Shao (Nature Portfolio, 2019)
Weak hybridization of two-dimensional metallic materials with their substrates plays a crucial role in charge transfer and doping characteristics. Here, the authors report heavy doping of monolayer 1H-TaS2 synthesized on Au(111) by ab-initio calculations and STM/STS experiments.